Medicinal Plants and their Potential Application in Health "Green Dentistry": A Literature Review - Lagos, Nayeli; Bernal, María; Espinoza-Carhuancho, Fran; Alvitez-Temoche, Daniel; Mauricio, Franco; Mayta-Tovalino, Frank (Odovtos - International Journal of Dental Sciences, 2024)
This study focuses on describing the potential use of medicinal plants in oral health. An electronic search was conducted in the PubMed and Scopus databases, limited to the last ten years. Key terms such as “phytodentistry”, “medicinal herbs”, “antimicrobials”, “dentistry”, “hygiene”, and “oral health” were used. In addition, a manual search was performed to verify the articles cited in the bibliographies of the initial documents and the websites of the corresponding journals were explored. The search strategy was specifically adapted for Scopus and PubMed. In this review, articles dealing with medicinal plants and their potential use in oral health were selected. The results of the reviewed studies were grouped into three main categories: plants with anti-inflammatory, antimicrobial, and healing properties. An overview of the main characteristics, materials used, and designs of the reviewed studies is provided. It was found that several medicinal plants, such as Aloe Vera, Turmeric, and Cocoa, have significant potential for use in oral health. These plants have proven to be effective in studies to improve oral health. However, further research is needed to confirm these findings and develop practical applications for their use in dentistry. This study underscores the importance of further exploring the potential of medicinal plants in promoting oral health.